Penyusunan Road Map Reformasi Birokrasi Pemerintah Kota Pekanbaru Tahun 2012-2017 - Cintia Pratiwi; Erman M. (Nakhoda: Jurnal Ilmu Pemerintahan, 2014)
This study , entitled " Preparation of Road Map Pekanbaru City Government Reforms Year 2012 - 2017 " This research is motivated by the Regulation of the Minister of Administrative Reform and Bureaucratic Reform No. 96 Year 2013 on the Establishment of Regional Pilot Project Reforms supported by the Local Government and Regulation of the Minister of Administrative Reform state No. 37 Year 2013 on Guidelines for Preparation of Road Map for local Government reforms , which in the regulation states that the Government of Pekanbaru City designated as one of the Bureaucratic Reform Pilot Project , and each region Pilot Project including Pekanbaru required to prepare Road Map reforms for term the next 5 years . Issues contained in this paper are still poor face Pekanbaru city government bureaucracy , lack of Quick Wins program in the preparation of the Road Map , lack of socialization Road Map bureaucratic reform and not the establishment of a special regional regulations governing the Road Map Pekanbaru City Government Reforms of 2012 -2017 . The method used in this study is a qualitative method that describes the descriptive data . Data collection techniques used were interviews , observation and document tracking . While the source of the data used is primary data obtained from the study site and supported by secondary data . Based on the results of research conducted there is some obstacle in the preparation of the Road Map is one of them happens tug of interest, lack of a strong commitment to the structures involved in the implementation of bureaucratic reform , there is a bottleneck in terms of the budget in the absence of specific regulations governing the area of the Road Map reform bureaucracy , having compiled a lack of socialization both internally and universal , the lack of quick wins in the Road Map , so that the step or action plan contained in the Road Map are repeat or hamier most of it is still the same as the program that has been done previously Pekanbaru city government .